LOCAL INNER DERIVATIONS ON THREE-DIMENSIONAL LIE ALGEBRAS - Alauadinov, A.K.; Jumaeva, Ch.I. (SCIENCE and SOCIETY, 2022)
In this paper we investigate local inner derivations of three-dimensional Lie algebras. We show that any local inner derivation of three-dimensional Lie algebras is an inner derivation.
Keywords: Lie algebra; derivation; inner derivation; local derivation; local inner derivation